2018
DOI: 10.4103/abr.abr_203_16
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Internet-based Cognitive Behavioral Therapy on the Anxiety Disorders among Adolescent Girls

Abstract: Background:The prevalence of anxiety disorders among children and adolescents are found to be approximately between 8–12 and 5–10, respectively, and the long-lasting effects of such disorders can expose the sufferers to impairment and dysfunction in several areas of life the examples of which are poor educational performance, low self-esteem, and depression. The present study aims to evaluate the efficacy of internet-based, cognitive-behavioral therapy (ICBT) in treating the anxiety disorders among adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Next, 53 full texts on digital interventions were examined from the living Metapsy database and three more studies were identified through reference tracking. All full texts were screened against our current eligibility criteria resulting in 21 RCTs for inclusion in the present meta-analysis (Figure 1; Mogoaşe et al, 2013; Tulbure et al, 2015; Yeung et al, 2017; Arjadi et al, 2018; Ciuca et al, 2018; Karbasi and Haratian, 2018; Yeung et al, 2018; Moeini et al, 2019; Jannati et al, 2020; Salamanca-Sanabria et al, 2020; Wang et al, 2020; Araya et al, 2021; Ghosh et al, 2023; Heim et al, 2021; Latif et al, 2021; Newman et al, 2021; Sun et al, 2021; Cuijpers et al, 2022; Zhao et al, 2022).
Figure 1. Flow chart of the studies selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…Next, 53 full texts on digital interventions were examined from the living Metapsy database and three more studies were identified through reference tracking. All full texts were screened against our current eligibility criteria resulting in 21 RCTs for inclusion in the present meta-analysis (Figure 1; Mogoaşe et al, 2013; Tulbure et al, 2015; Yeung et al, 2017; Arjadi et al, 2018; Ciuca et al, 2018; Karbasi and Haratian, 2018; Yeung et al, 2018; Moeini et al, 2019; Jannati et al, 2020; Salamanca-Sanabria et al, 2020; Wang et al, 2020; Araya et al, 2021; Ghosh et al, 2023; Heim et al, 2021; Latif et al, 2021; Newman et al, 2021; Sun et al, 2021; Cuijpers et al, 2022; Zhao et al, 2022).
Figure 1. Flow chart of the studies selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…To the results of this study and ours, if ketamine is combined with CBT in future studies, CBT will be more effective with the immediate impact of ketamine on concentration. [ 43 ] Furthermore, other studies have confirmed the effect of internet-based CBT on curing anxiety disorders. [ 44 45 46 ] Karbasi et al .…”
Section: Discussionmentioning
confidence: 97%
“…All selected publications were written in English, and no study about the subject was conducted in the Latin-American context. Interventions were administrated in Europe Flink et al, 2016;Lenhard et al, 2017;Nordh et al, 2021;Shahnavaz et al, 2017;Stjerneklar, Hougaard, McLellan, & Thastum, 2019;Topooco et al, 2019), United States (Murray et al, 2020;Palermo et al, 2018), Canada (Radomski et al, 2020), Australia (Donovan et al, 2017;March et al, 2018), and Iran (Karbasi & Haratian, 2018).…”
Section: Table 2 Main Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…The amount of weekly sessions that the adolescents were exposed to varied between five (Flink et al, 2016) and twelve (Lenhard et al, 2017;Shahnavaz et al, 2018). Amidst CBT's principals emphasized by the selected studies, the ones that stand out are: psychoeducation Lenhard et al, 2017), gradual exposure (Nordh et al, 2021;Shahnavaz et al, 2018), behavioral activation (Flinck et al, 2016;Topooco et al, 2019), relaxation techniques (Donovan et al, 2017;Karbasi & Haratian, 2018;March et al, 2018;Palermo et al, 2018), acquiring and implementing coping skills Flink et al, 2016;Murray et al, 2020), cognitive restructuring (Stjerneklar, Hougaard, McLellan, & Thastum, 2019;, relapse prevention (Lenhard et al, 2017;Murray et al, 2020), and assignment of homework tasks (Radomski et al, 2020;Shahnavaz et al, 2018).…”
Section: Table 2 Main Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation